Deprem etkisindeki yapılarda aktif ve pasif kontrol sistemlerinin uygulanması - Sarı, Barış (Fen Bilimleri Enstitüsü, 1998)
Deprem ve şiddetli rüzgar etkisinden dolayı oluşan titreşimlerin yapıya verdiği zararlardan korunmak amacıyla geliştirilen ve yirmibirinci yüzyılın yapı kavramını köklü bir şekilde değiştirecek olan akıllı binalarda kullanılan aktif ve pasif sismik kontrol sistemleri son yıllarda bir çok deprem uzmanının araştırma konusu olmuştur. Teknolojinin hızla ilerlemesi ve değişik materyallerin keşfedilip yapılarda uygulanması, yapıların dinamik yüklere karşı davranışında daha esnek ve uyumlu olmalarını sağlamıştır. Sismik yapı kontrolü aktif ve pasif olmak üzere iki ana gruba ayrılır. Dinamik dış yüklere karşı aktif kontrol uygulanan yapılarda depremin meydana getirdiği kesit zorlan ve yer değiştirmeler sensör denilen özel aygıtlarla ölçülerek kontrol bilgisayarına iletilir. Bilgisayarda işlenen veri sonucunda yapıda uygulanması gerekli kuvvetler aktuatör denilen harekete geçirici aletlere bilgi olarak iletilir. Aktuatörler de bu bilgi doğrultusunda gerekli karşı kuvvetleri uygular ve sistemde istenilen sönüm elde edilir. Yukarıda anlatılan işlem deprem sırasında devamlı tekrarlanır. Belli zaman aralıklarında sensörlerden veri alınır, işlenir ve kontrol kuvvetleri uygulanır. Böyle çevrime kapalı çevrim denir. Eğer aynı zamanda deprem şiddeti de sensörler tarafından ölçülüp veri olarak gönderilirse bu çevrime kapalı-açık çevrim denir. Sadece deprem titreşimlerinin dikkate alındığı sistemlere ise açık çevrim denir. Sistemler aktuatörün şekline göre de ayrılırlar. Aktuatörler, AMD sisteminde olduğu gibi yardımcı bir kütleden de oluşabilir veya diyagonal çubukların arasına konan ve kiriş gibi yapı elemanlarının altına bağlanan valf sisteminden de oluşabilir. Yardımcı kütle kullanan sistemlerde oluşturulacak kuvvet büyük çaplı olduğundan dolayı gerekli enerji miktarı da o denli büyük olmaktadır. Bu sebeble yapıda hazır bulundurulması gereken enerji sistemin maliyetini olumsuz yönde etkilemektedir. Valf sisteminde sadece küçük bir valfın açılıp kapanmasına yetecek enerji bulundurulduğundan dolayı yardımcı kütleli sisteme göre daha avantajlıdır. Valfin harekete geçme zamanı, kütleli sisteme göre daha kısadır ve böylece zaman kayıplarından dolayı yapının stabilitesinin bozulma riski azaltılmış olur. Kontrol sistemlerinde kullanılan malzemeler çok çeşitlidir. Piezoelektrik özellik taşıyan malzemeler herhangi bir mekanik kuvvete karşı elektrik akımı oluşturarak cevap verebilirler. Aynı şekilde bu durumun tersi; yani uygulanan elektrik akımına karşı mekanik bir kuvvetle cevap verebilme yetenekleri de vardır. Elektroreolojik sıvılar, uygulanan elektrik alanına göre kısa süre içinde viskozitesini değiştirerek sertleşirler. Bu malzemelerin yapılarda kullanılması yeni bir olgudur. Pasif kontrol sistemleri tasarlandıkları deprem şiddetleri için aktif sisteme göre iyi bir alternatif oluşturmaktadır. Maliyetinin düşüklüğü ve sistemin bakım gerektirmemesi dolasıyla büyük avantaj sağlarlar. Fakat sadece belli deprem seviyelerinde etkilidirler. Karma kontrol ise aktif kontrolün her deprem şiddetindeki etkinliğini ve pasif sistemin güvenilirliğini kendi bünyesinde barındırarak her iki sistemin avantajlarından yararlanılmasını sağlar. Ek bölümde ise harmonik yük uygulanan on serbestlik dereceli bir yay-kütle sisteminde herhangi bir serbestlik derecesindeki titreşimin sönümlenmesini sağlayan Visual Basic programı verilmiştir. Program sırasıyla verileri işler ve gerekli hesaplardan sonra çıktı olarak istenilen frekans değerinde uygulanması gerekli olan kontrol kuvvetlerinin değerini verir. Aktif ve pasif kontrol günlük hayatta yapılarda kullanılması bakımından yeni bir konudur. Ülkemizin deprem kuşağı üzerinde olduğu dikkate alınırsa, bu tür yeni sistemler üzerinde daha fazla araştırma yapılması, depremlerden dolayı oluşabilecek felaketlerin biraz olsun önüne geçilebilmesi açısından önem kazanmaktadır.

With progress toward a more sophisticated information oriented society, the functions of buildings have become complex and developed. This requires the building not only to be safer and more reliable but also to suffer less vibrations when subjected to earthquakes and strong winds. Vibration in structures can induce added displacement, stress and may result in significant damage. In last two decades, due to trend toward taller, more flexible and longer structures, under large enviromental loads such as strong winds and large earthquakes, excessive vibrational levels could be reached which result adversely affecting human comfort and even structural safety. In the current seismic design process, buildings are designed to provide sufficient lateral stiffness to assure serviceability, and sufficient strength to fulfill life safety requirements. Serviceability design considerations are also used for wind effects. The structural components of buildings in earthquake zones are designed to meet enveloping strength and stiffness demands computed from earthquake loads. A good design requires a balance between strength and stiffness. However this is difficult to achieve because strength and stiffness are coupled in terms of building components' geometry and properties. The intelligent building structure is a concept that describes structural systems that can supply on-demand-stiffness and on-demand-strength independently. Several intelligent structure concepts are presented in the literature. These concepts utilize active control to achieve their goals by providing sufficient lateral stiffness during high winds and minor earthquakes, and complementing structural strength only under moderate to large earthquakes to assure life safety. There are some limited experimental applications of intelligent building structures. However, real life applications of this technology require a total change in the way buildings are designed and constructed. In traditional design, structural stiffness is provided to limit interstorey displacements. During minor earthquakes, the structural viscous damping will bound the structural response. During moderate to major earthquakes, the building structure provides energy dissipation by yielding when the deformations exceed the elastic limits of the structure. If the building was designed with deficient strength, then the energy dissipation capacity of the structure may not be sufficient to prevent its collapse. The horizontal components of the earthquake ground motions are the most damaging to the building. For structural safety the buildings should be designed to separate Xll their natural frequencies from dominant seismic frequencies as well as from possible wind induced vibration frequencies. In this work, three types of basic control systems are described as listed below:. Active Structural Control Systems. Passive Control Systems (Base Isolation, Passive Energy Dissipation). Hybrid and Integrated Control Systems Active control of structures has been recognized as one of the most challenging and significant areas of research in structural engineering in recent years. Through the use of active controllers, a structure can modify its behavior during dynamic loadings such as impact, wind or earthquake loadings. Such structures with self-modification capabilities are called smart structures. The smart-structure technology will have enormous consequences in terms of preventing loss of life and damage to structure and its content specially for large structures with hundreds of members. The optimum design of the combined structure-control system can proceed along one of three paths: 1. The structure can be optimized and then active control devices can be implemented 2. The structure can be optimized with the active control devices in place. 3. The structure and active control devices can be optimized simultaneously. If a quick tour on the history of smart-structures is taken, we see that a series of research projects was conducted during the 1970' s on the response-controlled structure. The researchs probed more deeply the possibility of applying modern control theory, which had already been applied in the mechanical and electrical engineering fields, to the civil engineering field. Later, many types of active response control systems were proposed for civil engineering structures, and both theoretical analyses and practical experiments were conducted. These studies indicated that development of an active control system appropriate to each structure could achieve a very high vibration control effect because of its instantaneous response function. In particular, the open-closed loop control algorithm was proposed based on the uncertain nature of seismic disturbances. However, a complicated algorithm caused the control system to be complex, thus generating errors and instability. That is, these findings could not be adopted in actual complicated large-scale structures without further investigation. In 1989, the Active Mass Driver (AMD) system was pioneered and successfully installed in a new office building in midtown Tokyo. The aim of this system is to reduce building vibrations from mainly moderate and small earthquakes that occur frequently, and strong wind such as typhoons. Subsequent observations of earthquakes and strong winds have verified the effectiveness of the system. The AMD system uses the inertia of an auxiliary mass as the control force. The fundamental scheme of this system is based on an active tuned mass damper system. In designing the system, firstly, the closed loop algorithm was adopted. The feedback signal makes the system highly stable since it corresponds to the addition of a damping factor. Secondly, the control algorithm was simplified as much as possible. xm A simplified algorithm improves system reliability by reducing the possibility of errors. The ten-storey building with a height to width ratio 9.5 was chosen for the seismic response control. Because of its slenderness and weight eccentricity, the transverse and torsional directions were selected for control. The available space for installation was so restricted that one control force at the roof level was expected to suppress the response in one direction. The actuator operates the auxiliary mass and produces a control force which counters disturbances to the building. As an alternative to AMD, the non-resonant control type known as AVS (Active Variable Stiffness) is proposed. The system endeavours to produce a non-stationary, non-resonant condition in buildings during earthquakes. This condition is produced by altering the building's stiffness based on the nature of the earthquake, which changes continuously with time. The method is quite reasonable because it is designed to reduce the seismic energy input to buildings by non-resonance. As the non-resonant state is realized by changing the structure's structural stiffness with a mechanical system, the AVS system can be driven by only a small amount of power. This offers a solution to the energy problem in application of the active control system. In addition, as a result of its excellent technical innovation, the newly developed variable stiffness device can be activated by a small amount of power. Thus, it possesses the excellent advantage that it can realize effective control even during extremely severe earthquakes. Starting with basic research, including feasibility studies, the various hardwares that compose the AVS system were developed independently always with the intent of practical application. Moreover, the particular characteristics of these hardwares have been verified by shaking table tests and dynamic loading experiments, and in 1990 the AVS system was first applied on a trial basis to a three-storey steel building. The effectiveness of the applied system has since been verified by tests and observations. In AVS system, the variable stiffness devices (VSD) are installed between the brace tops and the lateral beams. In brief, the VSD can work in two ways, i.e. to lock (engage: brace becomes effective) or to unlock (release: brace becomes ineffective) the connection condition between the brace and the beam. The open/closed function of VSD is cntrolled by oil movements.therein, thus locking or unlocking the connection condition between the beam and the braces, and producing two alternative stiffnesses at each floor. The design load is determined by considering the design shear force, and the maximum strength is two times the design load. Cable-stayed bridges, being prone to have many types of vibrations, offer a wide area of research in the control field, which until now has been approached for practical applications mainly by passive means. Another challenging possibility is active control; the structure can be made more economical by releasing some of the design constraints and be more stable against dynamic loads. Cables are very efficient structural members due to their high strength and light weight and their use has been increased significantly in civil engineering structures such as cable- stayed bridges, guy towers, transmission lines and cable-supported roofs. Cables are flexible and their inherent damping is extremely small and consequently, vibration with large amplitudes can be easily induced by external disturbances such as wind. Also large cable XIV vibration can be induced by internal resonance; large vibrations of some cables in a pedestrian bridge were induced by the lateral girder vibration during crossing of a large number of pedestrians. Large cable vibrations develope minor cracks around the anchor joints of the cables in many cable-stayed bridges and corrosion protection systems were thus damaged; this may lead to failure of the cable. Although significant success has been achieved towards practical application of active control, there exists a myriad of problems, solutions to which are very important before the concept can be succesfully realized. Time delay in control feedback is one of the problems which needs a serious attention. Time delay occurs mainly because of: 1. Time taken in on-line data acquisition from sensors at different locations of structure. 2. Time taken in filtering, processing of these data for required control force calculation and transmission of the control force signal to the actuator. 3. Time taken by the actuator in building up the required control force. Because of the time delay, unsynchronized control force may be applied to the structure which may cause degradation in the efficiency of control or may even render the structure unstable. The peak power and total energy requirements of conventional devices such as active tendons and AMDs can be extremely large. Unfortunately, the time at which control power is most needed often coincides with the time at which failure of most public utility systems and distribution networks can be expected. This raises a serious concern over the availability of adequate power and energy sources for the active control of seismically excited structures. To economize the energy expense associated with seismic structural control, the application of high-energy, short duration control force pulses has been proposed as an alternative to methods that apply continuous control action. More recently, Ghaboussi and Paul (1992) proposed an innovative, active control mechanism, termed gravity actuators, that is designed to alleviate the energy concerns associated with conventional devices. In seismic control applications, these actuators use the reserved kinetic energy stored in suspended masses to generate lateral forces for control. The gravity-actuator control system is thus capable of providing active protection to structures under seismic excitations with a minimal external energy demand. Moreover, the proposed system is designed to furnish comfort control to structures experiencing wind generated motions. Gravity actuators are an innovative control mechanism designed to provide active protection to structure subjected to seismic ground motion with a minimal energy requirement.the actuator consists of an auxiliary mass, free to move in the vertical direction. The mass is connected to an elastic cable that passes over two pulleys and is anchored to the actuator base assembly. This base assembly is comprised of a reel that stores an additional wound length of cable and a motor-brake unit capable of releasing, catching and accelerating the reel and thus the auxiliary mass. Individual gravity actuators are deployed in pairs, with one actuator placed on each side of the frame, to form the complete gravity actuator system. Bidirectional control is achieved by aligning a pair of actuators along each of the two major axes of the structure. One XV method proposed for varying the cable tensions is to accelerate the masses up and down by winding and unwinding the reel at the actuator base. An alternative, less energy intensive method of producing a net horizontal control force couple is to successively release and catch the masses. This is accomplished by releasing and catching the reels with the brake component of the actuator base assembly. In chapter 4 of this work, it is described about the various types of materials used in active and passive control. The most common material is the piezoelectric ceramic and film layer applied to sensors and actuators. The most prominent actuation techniques that been examined in recent projects have been based on the properties of piezelectric ceramics and films, shape memory alloys (such as nitinol), electrorheological fluids and, to some extent, magneto strictive devices. No single actuation technique may offer the solution to every technical need, so it may be convenient and even necessary to consider hybrid actuators formed by combining in some clever manner the properties of two or more actuating substances. For instance, a suitable combination of a piezoelectric ceramic and an electrorheological fluid may offer the most satisfactory solution in a given situation. Piezoelectric or electroelastic materials have been used for a long time in various types of communication equipment. In smart structures, such materials can be used as actuators and sensors. At the last chapter, the passive and hybrid structural systems were described. Base isolation is becoming widely accepted as a design strategy for low-rise buildings in seismic regions. The idea behind base isolation is very simple. This technique involves the separation of the superstructure using reinforced elastomeric isolators. While base isolation systems are effective for protecting seismic excited buildings this system provides an economic alternative for the seismic design of new structures and the rehabilitation of existing buildings and bridges. Passive systems are limited to low-rise buildings. For tall buildings, uplift forces may be generated in the isolation system leading to an instability failure. The passive system is not feasible for seismic excited tall buildings because of the overturning phenomenon. A medium rise building, even when isolated, could potentially generate overturning moments that would cause uplift of some isolators. Base isolation has not been proposed for taller buildings because of the obvious problems of uplift leading to overturning and the difficulty of achieving a reasonable period shift, for more flexible, longer period structures. Passive energy dissipating devices can be used within a structural system to absorb seismic energy. These devices are capable of producing significant reductions of interstory drifts in moment-resisting frames. The energy is dissipated either yielding of the mild steel, sliding friction, motion of a piston within a viscous fluid, orificing of fluid or viscoelastic action in polymeric materials. At last, the idea of hybrid control system is to utilize the advantages of both the passive and active control systems to extend the range of applicability of control systems to protect the integrity of the structure.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1998
Keywords: Denetim sistemleri; Deprem; Control systems; Earthquake